Systemic Candidosis in Dogs Associated with Canine Distemper Virus - Alves, Rodrigo Cruz; Carneiro, Rosileide dos Santos; Kommers, Glaucia Denise; de Souza, Almir Pereira; de Galiza, Glauco José Nogueira; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2020)
Background: Candidosis is an opportunistic fungal infection caused by yeasts of the genus Candida, which normally reside on the surfaces of the mucous membranes and in the skin of several animal species and healthy humans; however the fungi can convert into pathogenic microorganisms and result in invasive infections with systemic involvement due to the impairment of the immune system. Systemic candidosis is rare in dogs and few reports of this mycosis are available in literature. Therefore, the objective of this study was to describe three cases of systemic candidiasis associated to canine distemper in dogs, highlighting the main epidemiological, clinical and pathological aspects. Cases: Three cases of systemic infection by Candida sp. were diagnosed in dogs. The animals predominantly presented neurological clinical manifestations, followed by unspecific alterations with an evolution of 5 to 30 days. Macroscopically, the lesions were characterized by white-yellowish multifocal to coalescent areas surrounded by reddish borders in the kidneys and heart (cases 1, 2 and 3); liver and submandibular lymph node (case 1); and lung (case 2). In the brains of the three dogs were observed multifocal, blackened and/or reddish and friable areas. In case 1, was observed an increased volume of the right carpometacarpal joint, that when cut, released a reddish and turbid content. In case 2, there was deposition of a whitish lumpy material on the epicardial surface, aorta artery, pericardial sac and spleen; infarction on the right testicle, hydroureter, pyelonephritis and hydronephrosis. Microscopically, the lesions consisted of necrossupurative inflammation associated to hemorrhage, vasculitis, congestion, thrombosis, infarction and fungal structures with distinct morphological patterns which included blastoconidia, pseudohyphae and hyphae. The fungal structures were strongly positive for the anti-Candida albicans polyclonal antibody in the immunohistochemistry. All 3 dogs were concomitantly infected by the canine distemper virus, and 2 of the animals also presented other comorbidities. Discussion: The diagnosis of systemic candidiasis was made based on the morphotintorial characteristics of the agent and confirmed by immunohistochemistry. The yeasts of the genus Candida live as commensals, but when there is an imbalance of the normal microbiota or the immune system of the host is impaired, the yeasts can convert themselves into opportunistic pathogenic microorganisms. The concomitant infection with the canine distemper virus may have favored the infection and proliferation of the agent in the tissues, as the virus causes immunosuppression. The extensive vascular lesions associated to fungi in the vascular lumen and wall observed in the affected organs suggest hematogenous dissemination causing acute infarctions. The clinical signs of systemic candidosis are extremely variable and reflect the affected organs and hardly ever the infections are considered in the differential diagnoses. The dogs presented neurological clinical signs compatible with canine distemper, however the other clinical alterations were unspecific and insufficient to correlate with a secondary infection and none of the cases diagnosed in the necroscopic examination suggested systemic candidiasis during the clinical investigation. The histochemical methods used in this study contributed effectively for the prior diagnosis of candidosis, making evident the variable morphological characteristics of the fungi. It is concluded that the systemic candidosis in dogs with canine distemper affects young and adult animals with predominantly neurological and unspecific clinical signs resulting from necrossupurative and vascular lesions in several organs, including the articular involvement little described in dogs and testicular lesions only reported in humans.